1986
DOI: 10.1093/nar/14.3.1253
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of viral DNA forms inNicotiana plumbaginifoliaprotoplasts inoculated with cassava latent virus (CLV); evidence for the independent replication of one component of the CLV genome

Abstract: Totipotent leaf mesophyll protoplasts of Nicotiana plumbaginifolia, Viviani were inoculated with cassava latent virus (CLV) or with full length copies of CLV genomic DNAs 1 and 2 excised from replicative forms of M13 clones. Virus specific DNAs began to appear 48-72h after inoculation with virus or cloned DNAs, coincident with the onset of host cell division. Infected cells accumulated supercoiled forms of DNAs 1 and 2 as well as progeny single-stranded (ss) virion (+) sense DNAs representing each component of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(47 citation statements)
references
References 16 publications
2
45
0
Order By: Relevance
“…Approximately 107 protoplasts were inoculated with 50 ~tg of purified clone insert by electroporation and aliquots containing approximately 2 × 106 protoplasts were cultured at 25 °C in the medium of Nagata & Takebe (1971). Protoplasts were harvested as described by Townsend et al (1986) and total nucleic acids were extracted by the method of Covey & Hull (1981).…”
Section: Replication In Protoplastsmentioning
confidence: 99%
“…Approximately 107 protoplasts were inoculated with 50 ~tg of purified clone insert by electroporation and aliquots containing approximately 2 × 106 protoplasts were cultured at 25 °C in the medium of Nagata & Takebe (1971). Protoplasts were harvested as described by Townsend et al (1986) and total nucleic acids were extracted by the method of Covey & Hull (1981).…”
Section: Replication In Protoplastsmentioning
confidence: 99%
“…Two genomic components (DNAs A and B) are essential for systemic infection (Stanley, 1983;Stanley & Gay, 1983) and genetic analysis has revealed that DNA A is responsible for viral DNA replication, coat protein synthesis and the production of virus particles (Townsend et al, 1985(Townsend et al, , 1986Klinkenberg & Stanley, 1990) while DNA B is required for cell-to-cell and systemic movement of virus (von Arnim et al, 1993). The genomic components have a highly conserved sequence of approximately 200 nucleotides (common region) that is located within their intergenic regions (Stanley & Gay, 1983).…”
mentioning
confidence: 99%
“…When introduced into protoplasts it is capable of self-replication to produce both ss and ds DNA forms typical of infection which showed that the genes responsible for its replication are in this component (Townsend et al, 1986). Because both components are required for systemic infection in plants (Stanley, 1983), DNA B gene products are implicated in spread of the virus or viral DNA throughout the plant (Townsend et al, 1986;Etessami et al, 1988). In contrast to ACMV, beet curly top virus (BCTV) has a single genomic component, organized similarly to ACMV DNA A .…”
mentioning
confidence: 99%